2005
DOI: 10.1080/10256010500230171
|View full text |Cite
|
Sign up to set email alerts
|

Soil δ15N patterns in old-growth forests of southern Chile as integrator for N-cycling

Abstract: Old-growth forests of southern Chile represent an important reserve of temperate (rain) forests in the world. Wetter and colder forest ecosystems appear to be more efficient in conserving and recycling N such that mostly non-plant available N species are lost, which could be indicated by more depleted delta15N values of the soil and plants. Hydrological N loss from the old-growth forests in southern Chile occurs mainly via dissolved organic nitrogen and not via dissolved inorganic N. Forest disturbances (e.g. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 29 publications
4
41
0
Order By: Relevance
“…EVects of Wres on nitrogen isotopic signatures are however complex, since the eVect appears negligible below a temperature of 200°C and above a temperature of 600°C (Saito et al 2007). Enhanced nitriWcation rates after wildWres may potentially result in 15 N enrichment, especially in the upper soil layers (Boeckx et al 2005). In boreal forests, wildWres can lead to pulses of NO 3 losses, and increased NO 3 concentrations in the humus layer can remain for longer time periods (DeLuca et al 2002).…”
Section: Mechanisms For Soil Organic Matter 15 N Enrichmentmentioning
confidence: 99%
“…EVects of Wres on nitrogen isotopic signatures are however complex, since the eVect appears negligible below a temperature of 200°C and above a temperature of 600°C (Saito et al 2007). Enhanced nitriWcation rates after wildWres may potentially result in 15 N enrichment, especially in the upper soil layers (Boeckx et al 2005). In boreal forests, wildWres can lead to pulses of NO 3 losses, and increased NO 3 concentrations in the humus layer can remain for longer time periods (DeLuca et al 2002).…”
Section: Mechanisms For Soil Organic Matter 15 N Enrichmentmentioning
confidence: 99%
“…In a wood charring experiment (non-oxygen atmosphere) at 150, 340, and 480 • C, Czimczik et al (2002) observed an enrichment of δ 13 C at 150 • C where there was no C concentration change but a depletion of δ 13 C at 340 and 480 • C, with charring where the C concentration increased over 50 % due to charring. Fires tend to lead to enrichment of 15 N. This is particularly observed in soils immediately in the aftermath of fires (Boeckx et al, 2005;Grogan et al, 2000;Herman and Rundel, 1989;Huber et al, 2013), but there is limited information available on the exact temperature ranges that cause specific levels of 15 N enrichment. In this study, we observed enrichment of 15 N up to 350 • C and depletion after 350 • C for all soils (Fig.…”
Section: Changes In Som Concentration Distribution and Compositionmentioning
confidence: 99%
“…The species diversity, biogeochemical cycles, productivity and carbon (C) sequestration of forest ecosystems are largely regulated by nitrogen (N) dynamics via plant uptake, soil N transformation and loss (Perakis and Hedin 2002;Frey et al 2004;Boeckx et al 2005;Luyssaert et al 2008). Chronic atmospheric N deposition can obviously alter N transformation and loss processes, such as mineralization Chen and Högberg 2006), nitrification (Fenn et al 1998;Venterea et al 2004), ammonia volatilization (Huygens et al 2007) and N 2 O emission (Venterea et al 2003;Zhang et al 2008a), as well as organic and inorganic N losses (McDowell et al 2004;Fang et al 2009a, b), and their responses depend on ecosystem N saturation status .…”
Section: Introductionmentioning
confidence: 99%